How to deal with Crisis knowing Change Management Principles - Eduard Ceptureanu; Sebastian Ceptureanu (Revista de Management Comparat International)
International crisis, market transparency, labor mobility, global capital flows, and instantaneous communications have blown scenario that senior executives in large companies had a simple goal for themselves and their organizations: stability.